How to Improve Awareness, Treatment, and Control of Hypertension in Africa, and How to Reduce Its Consequences: A Call to Action From the World Hypertension League. Issue 9 (31st May 2022) - Parati, Gianfranco; Lackland, Daniel T.; Campbell, Norman R.C.; Ojo Owolabi, Mayowa; Bavuma, Charlotte; Mamoun Beheiry, Hind; Dzudie, Anastase; Ibrahim, M. Moshen; El Aroussy, Wafaa; Singh, Sandhya; Varghese, Cherian V.; Whelton, Paul K.; et al.
Abstract : Hypertension is the leading preventable risk factor for cardiovascular diseases and disability globally. In low- and middle-income countries hypertension has a major social impact, increasing the disease burden and costs for national health systems. The present call to action aims to stimulate all African countries to adopt several solutions to achieve better hypertension management. The following 3 goals should be achieved in Africa by 2030: (1) 80% of adults with high blood pressure in Africa are diagnosed; (2) 80% of diagnosed hypertensives, that is, 64% of all hypertensives, are treated; and (3) 80% of treated hypertensive patients are controlled. To achieve these aims, we call on individuals and organizations from government, private sector, health care, and civil society in Africa and indeed on all Africans to undertake a few specific high priority actions. The aim is to improve the detection, diagnosis, management, and control of hypertension, now considered to be the leading preventable killer in Africa.